KONTENPLASI MASYARAKAT MUSLIM MELAYU PALEMBANG DALAM TANTANGAN EKONOMI GLOBAL - Raden Ayu Erika Septiana; Raden Ayu Ritawati (Majalah Ilmiah Tabuah: Ta`limat, Budaya, Agama dan Humaniora, 2019)
Along with the fast flow of change and the strong acculturation process of Palembang Malay Muslim community, Malay culture is like a ship that sails in the middle of a storm. This is based on the fact that our development places too much emphasis on material aspects that have given birth to an imbalance in the behavior patterns of the Palembang Malay Muslim community, which has increasingly been eroded by economic globalization. Excessive material competition has produced anomicous societies. The embodiment of the way the Palembang Malays behave is also reflected in their work ethic which can be roughly seen from the social structure and norms of the community. The purpose of this study is to determine the extent to which the global economy has the potential to obscure the Malay identity and the pure Muslim identity. The qualitative approach was chosen using the method of field research carried out in an effort to understand the symptoms in such a way as a phenomenon that is not external expressed through their views. The results of this study found the fact that enthusiasm and work ethic were actually not reflected in most Palembang Malay Muslim communities. Malay and Islamic relations actually obscure the role and competitiveness of the community in the practice of social relations and in earning a living. Religion is still considered as an element of local culture which is concentrated in the form of traditional customary behavior, not as a foothold, direction and way of life. Indeed religion serves to encourage humans to get involved in economic roles and behavior, because religion can reduce anxiety and fear not too found in this study. Where the aftereffect of this condition arises a generation that is deprived of values, a generation that is fragile from the spiritual aspect, easily influenced, not easily cared for and loses its cultural footing.